Analisis Gaya Kepemimpinan dan Lingkungan Kerja Non Fisik terhadap Kinerja Pegawai Melalui Kepuasan Kerja - Titi Astutiningtyas; Kusuma Chandra; Gendro Wiyono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to analyze the relationship between leadership style and non-physical work environment on employee performance through job satisfaction as an intervening variable for employees of BBTKLPP Yogyakarta. This research method uses quantitative descriptive using primary data obtained from distributing questionnaires. In this study using the sesnus technique, where all populations are taken, each population has the same opportunity to be sampled. The number of samples taken in this study were 110 questionnaires. Data were analyzed using SPSS and Smart PLS. The results showed that leadership style had a positive and significant effect on job satisfaction with a significance level of 0.042 <0.05, so hypothesis I was accepted. The non-physical work environment has a positive and significant effect on job satisfaction with a significance level of 0.000 <0.05, so hypothesis II is accepted. Leadership style has no positive and significant effect on employee performance with a significance level of 0.455 > 0.05, so hypothesis III is rejected. Non-fictional work environment has no positive and significant effect on employee performance with a significance level of 0.256 > 0.05, so hypothesis IV is rejected. Job satisfaction has a positive and significant effect on employee performance with a significance level of 0.006 < 0.05 (p <0.05), so hypothesis V is accepted. Leadership style on employee performance with job satisfaction as an intervening variable with a significance level of Z score 1.57 < 1.96 then hypothesis VI is rejected. Non-physical work environment on employee performance with job satisfaction as an intervening variable with a significance level of Z score 2.51> 1.96 then hypothesis VII is accepted. Keywords: Leadership style, non-physical work environment, job satisfaction, employee performance.